Drug sensitivity pattern of microorganisms of infected wounds at TUTH - Singh, A.; Vaidya, P.; Tuladhar, N.R.; Maharjan, S. (Journal of Institute of Medicine Nepal, 2007)
Introduction: The spread of antibiotic resistance and the appearance of multiple antibiotic resistant pathogens have been recognized by the WHO as a serious problem that complicates medical treatment of bacterial infections. Present study is a retrospective study from 15June to to 15th December 2004, which includes 1379 pus samples. Methods: Culture and sensitivity testing for pus samples was done using standard Microbiological protocol in TUTH microbiology laboratory. Results: We found that Staphylococcus aureus is the commonest isolate (57.25) followed by E. Coli (15.61) The most effective antibiotic in-vitro for Staphylococcus aureus is Cloxacillin (87.0) followed closely by Erythromycin (81.8). In E. coli, the most effective antibiotics was Amikacin (77.88). Pseudomonas was isolated in only in (5.83) cases. The most effective antibiotic in vitro was Amikacin (47.22) and Ciprofloxacin (47.22) followed by Gentamycin (32.6). Conclusion: With rampant antibiotic use, the drugs become resistant of which the clinicians may not be aware. Similarly, the organism pattern may differ in different hospitals. So, we believe that such regular update to our clinicians will help them use appropriate antibiotics, as they will be aware of the prevalent organism and the most effective antibiotic to it. Journal of Institute of Medicine Vol.28(1) 2006